High Performance Anode-Supported Solid Oxide Fuel Cells with Thin Film Yttria-Stabilized Zirconia Membrane Prepared by Aerosol-Assisted Chemical Vapor Deposition - Jang, Dong Young; Kim, Manjin; Kim, Jun Woo; Bae, Kiho; Son, Ji-won; Schlupp, Meike V. F.; Shim, Joon Hyung (ELECTROCHEMICAL SOC INC, 2017)
In this study, we have successfully fabricated yttria-stabilized zirconia (YSZ) electrolyte thin films by aerosol-assisted chemical vapor deposition (AACVD) for solid oxide fuel cells (SOFCs) working at an intermediate temperature range under 600. degrees C. The mix ratio of precursor sources and the deposition temperature of the AACVD process are optimized to obtain target composition and crystal structure of the YSZ film. The optimized AACVD YSZ membrane is incorporated onto Ni-YSZ anodes supported without interlayers for evaluation of SOFC performance. Fully dense 1-mu m-thick AACVD YSZ electrolyte successfully produces a stable open circuit voltage (OCV) greater than 1 V at all test temperatures in the range of 450- 600. degrees C. Power output of the test cell is measured as about 600 mW cm(-2) at 600. degrees C. Performance of our cell is compared to that of a reference cell with the same structure but with an 8-mu m-thick membrane produced by screen-printing; our cell produces 1.4 to 4 times as much power as the reference cell at all test temperatures. Electrochemical impedance analysis has confirmed that the power enhancement with the thin AACVD YSZ membrane is due to effective reduction of both ohmic and polarization resistances. (C) 2017 The Electrochemical Society. All rights reserved.
Keywords: LOW-TEMPERATURE PERFORMANCE; ATOMIC LAYER DEPOSITION; PULSED-LASER DEPOSITION; ELECTROLYTE; CONDUCTIVITY; FABRICATION; MICROSTRUCTURE; IMPACT; SOFC; YSZ